The use of a salmonella bacteriophage in bearded dragons: application, passage time and reisolation - Renfert, Kevin; Rabsch, Wolfgang; Fruth, Angelika; Speck, Stephanie; Pees, Michael (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2019)
Objective This study determined the passage time and phage propagation time of a salmonella specific phage, Felix O1, in bearded dragons, based on reisolation from cloacal swabs and faecal samples following oral administration, as a possible tool for reducing the zoonotic risk of salmonella from pet reptiles. An application scheme for this phage in bearded dragons was developed.Material and methods Ten healthy bearded dragons (Pogona vitticeps) were used in the study. The pH tolerance of the phage was tested and drugs were used to evaluate their influence on the gastric pH of the reptiles. After pH adjustment, the phage was administered orally for 12 consecutive days. Over 60 days, swabs were taken from the cloaca and examined for the presence of phages using culture and PCR. Furthermore, faecal samples were collected for phage quantification.Results Felix O1 displayed no activity at pH below 2.8. A calcium- and magnesium carbonate buffer induced an appropriate gastric pH increase for 30 minutes. Phages were reisolated for up to 24 days (mean shedding: 19 days) after last administration. Titres between 105 and 107 plaque forming units/g faeces were detected. The animals did not show any clinical signs related to phage application.Conclusion and clinical relevance The study provides first results on oral administration, passage time, and reisolation of a phage in reptiles. It could be shown that the phage was able to replicate in the intestine, and was shed for a prolonged period and therefore could potentially contribute to a reduction of salmonella shedding.
Keywords: Reptile; salmonella; phage; PCR